PEMANFAATAN PERPUSTAKAAN KELILING DALAM MENUMBUHKAN MINAT BACA ANAK USIA DINI - Rahimah Rahimah (Jurnal Pustaka Ilmiah, 2018)
The formulation of the problem in this study is how to use mobile library services in growing interest in reading early childhood. The purpose is to find a solution to the problems experienced by the community now about how to foster interest in reading for early childhood. Especially among schools, in an effort to overcome the low interest in reading. Interest in reading alone has a big role in the progress of a nation. Now when we see the fact that our country is a country that is still very low in reading interest compared to other countries, especially neighboring countries. So that interest in reading is the key to advancing a nation, it is important to know that mastery in the knowledge of technology and communication can only be enjoyed by a high interest in reading. And those who participated in the foremost role in fostering reading interest included family, community, and educational institutions in the community. The presence of a mobile library will make children interest in reading. Kelilign library has several benefits for readers, namely: a) the library itself is able to grow a variety of knowledge in children. b) and with the library there will be a love for books and reading in children. c) with the library intelligence in children will increase. d) libraries can enrich children’s insights and experiences. e) disputes can be used as a tool in the child’s learning process. f) and with the library there will be a sense of responsibility for children.